2021
DOI: 10.3390/ijerph18052470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Mental Health in Adolescents: A Systematic Review

Abstract: Due to lack of sufficient data on the psychological toll of the COVID-19 pandemic on adolescent mental health, this systematic analysis aims to evaluate the impact of the pandemic on adolescent mental health. This study follows the PRISMA guidelines for systematic reviews of 16 quantitative studies conducted in 2019–2021 with 40,076 participants. Globally, adolescents of varying backgrounds experience higher rates of anxiety, depression, and stress due to the pandemic. Secondly, adolescents also have a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
528
8
36

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 653 publications
(602 citation statements)
references
References 31 publications
30
528
8
36
Order By: Relevance
“…Young people, in particular, reported low scores on psychological wellbeing tests due to the pandemic. This finding is in line with a recent study [ 24 ] and also with a systematic review about adolescence [ 37 ]. It is notable considering that COVID-19 has much more serious consequences on the health of older people, who reported no negative psychological health scores.…”
Section: Discussionsupporting
confidence: 93%
“…Young people, in particular, reported low scores on psychological wellbeing tests due to the pandemic. This finding is in line with a recent study [ 24 ] and also with a systematic review about adolescence [ 37 ]. It is notable considering that COVID-19 has much more serious consequences on the health of older people, who reported no negative psychological health scores.…”
Section: Discussionsupporting
confidence: 93%
“…Distinct psychological impacts of the COVID-19 pandemic are not only experienced among older adults but also among adolescents. Multiple studies have reported increased levels of anxiety, depression, and stress among adolescents during this pandemic [ 12 , 13 ]. While anyone can be infected with COVID-19, older adults, those who are immuno-compromised, and people with pre-existing chronic medical conditions are at increased risk of severe illness [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given this context, when Michigan Governor Gretchen Whitmer mandated closure of all K-12 school buildings across the state on March 16, 2020Whitmer-Executive Order, 2020-35), students were left without physical access to an important source of mental health care (Lee and Ward, 2020). At the same time, the COVID-19 pandemic brought about unparalleled shifts in social circumstances, such as social distancing and quarantine guidelines (CDC, 2020), that contributed to increased social isolation and decreased social support for students, further impacting mental health (Jones et al, 2021). These changes highlighted the important role that mental health care often plays in promoting learning, as seen through the development of school-based mental health in the 1990s, and renewed calls to prioritize mental health delivery in the school setting in response to its sudden in-person absence (Flaherty and Osher, 2003;Weir, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For educators and school staff, COVID-19 school closures produced a number of new challenges in the delivery of mental health support. For example, in a sample of 583 adolescents (80% female, 71% White) surveyed between April 27 and July 13, 2020, symptoms of depression were reported among 55%, anxiety among 48%, and Post-Traumatic Stress among 45% (Jones et al, 2021;Murata et al, 2021;Zhou S.-J. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation